1997
DOI: 10.2172/464193
|View full text |Cite
|
Sign up to set email alerts
|

An experimental scale-model study of seismic response of an underground opening in jointed rock mass

Abstract: NRC Job Code B6643 ST For sale by the U.S. Government F'rinting Office Superintendent of Documenb, M a i l Stop: SSOP, Washington, DC 20402-9328 ISBN 0-16-048982-2 Portions of this document may be illegible in electronic image products. Images are produced from the best available original document. ABSTRACTThis report describes an experimental investigation conducted by the Center for Nuclear Waste Regulatory Analyses (CNWRA) to (i) obtain a better understanding of the seismic response of an underground openin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The welded tuffs at Yucca Mountain, including the welded Topopah Spring tuff that would be the host rock for emplacement drifts, are highly fractured. Through research conducted by the Center for Nuclear Waste Regulatory Analyses and others, significant progress has been made recently in understanding the seismic behavior of jointed rock masses and in developing rock joint models for cyclic loads (e.g., Fishman 1988;Jing et al 1992;Huang et al 1993;Qiu et al 1993;Wibowo et al 1993;Hsiung et al 1994a;Hsuing et al 1994b;Ghosh et al 1995;Kana et al 1995;Souley et al 1995). However, this research has also clearly shown that dynamic joint behavior is a complex nonlinear phenomenon that depends on the joint boundary conditions, joint surface characteristics, and joint slip history.…”
Section: A21 Repetitive Seismic Loads and Drift Stabilitymentioning
confidence: 99%
“…The welded tuffs at Yucca Mountain, including the welded Topopah Spring tuff that would be the host rock for emplacement drifts, are highly fractured. Through research conducted by the Center for Nuclear Waste Regulatory Analyses and others, significant progress has been made recently in understanding the seismic behavior of jointed rock masses and in developing rock joint models for cyclic loads (e.g., Fishman 1988;Jing et al 1992;Huang et al 1993;Qiu et al 1993;Wibowo et al 1993;Hsiung et al 1994a;Hsuing et al 1994b;Ghosh et al 1995;Kana et al 1995;Souley et al 1995). However, this research has also clearly shown that dynamic joint behavior is a complex nonlinear phenomenon that depends on the joint boundary conditions, joint surface characteristics, and joint slip history.…”
Section: A21 Repetitive Seismic Loads and Drift Stabilitymentioning
confidence: 99%
“…both cyclic pseudostatic and dynamic loadings. A detailed discussion regarding the design of this scale-model experiment is given by Kana et al (1995).…”
Section: Dynamic Scale-model Experiments Of a Jointed Rock Massmentioning
confidence: 99%
“…In and p represents the model and the prototype parameters, where k is equal to 2.0, which was determined by comparison of the shear test results of the simulated rock interfaces and actual rock joints. For a detailed discussion regarding the shear tests of the simulated rock interfaces, readers are referred to a separate report prepared by Kana et al (1995). Finally,…”
Section: Dynamic Scale-model Experiments Of a Jointed Rock Massmentioning
confidence: 99%
See 2 more Smart Citations